Favorable benefits of autologous serum therapy in chronic spontaneous urticaria - Shantharaju, Sanjana Agrahara; Hongal, Amrita; Gupta, Diksha; Jonnagadla, Girishma (UI Scholars Hub, 2023)
Background: In chronic spontaneous urticaria (CSU), autologous serum therapy (AST) is an alternative treatment modality that provides promising benefit of extended relief period without side effects and economic burden of pills. This study aimed to assesses the efficacy of AST in CSU patients irrespective of their autologous serum skin test (ASST) result. Methods: Patients were enrolled based on inclusion and exclusion criteria after taking written informed consent. A detailed history and clinical examination & relevant investigations were done. ASST was performed and irrespective of the test result AST was given to all study subjects that included weekly intramuscular injections for 8 times. Urticaria activity score (UAS), urticaria severity score (USS) and dermatology life quality index (DLQI) were recorded at baseline and 8th visit to note the improvement in the condition. Result: Among 34 patients, 24 patients (70.58%) had a positive ASST result while 10 (29.41%) were negative. In 24 patients with positive ASST result, the average UAS, USS, & DLQI was 2.95, 20.45, & 6.6 respectively at baseline and improved to 0.29, 1.83, & 0.45 respectively at week 8. In 10 patients with negative ASST, the average UAS, USS, and DLQI was 2.4, 20.9, & 8 respectively at baseline and improved to 0.4, 2.8, & 0.6 respectively at week 8 after AST. Irrespective of ASST result, improvement was observed in UAS, USS, & DLQI, which is statistically significant. Conclusion: AST is a beneficial alternative therapy in CSU patients with partial control of symptoms with pills.